The Factors in the use of WhatsApp applications in education management in IPTA: a pilot study - Balasundran, Komathy; Yunus, Jamal Nordin; Nallaluthan, Kesavan; Martin, Tulasi (Global Advances in Business Studies, 2023)
In terms of educational management, the WhatsApp application is very popular among the lecturers. Lecturers, on the other hand, were found to be uninterested in using WhatsApp for educational management. The majority of WhatsApp research has focused on students in the context of learning, while this study will focus on educational management among public university lecturers. Before conducting more in-depth research, the goal of this study is to describe the pilot testing method for the proposed model. A pilot study was done to assess the survey questionnaire's applicability and reliability. The data was gathered from 100 Malaysian public university lecturers via an online survey. Before beginning the actual study, the researcher discusses the pilot testing process and methodology that will contribute to the research in this context. The Unified Theory of Acceptance and Technology Use (UTAUT) model has been applied to the proposed new model. The results of the pilot study agreed that Cronbach's alpha ranged from 0.829 to 0.900 for most of the constructs in the proposed model, indicating that they were reliable. As a result, the constructs in the questionnaire are suitable for larger-scale research in the future. The findings of this study are beneficial to the Ministry of Higher Education in determining the reasons for lecturers' use of WhatsApp, including whether they use it for social purposes, to obtain or share information related to university educational management, or to improve the lecture process.